The relationship between renewable energy consumption, trade openness and economic growth: The case of Bosnia and Herzegovina - Yılmaz Onur Ari\. (Economic Review: Journal of Economics and Business, 2020)
The paper examines the renewable energy con- sumption-trade openness-economic growth ne- xus for Bosnia and Herzegovina using annual time series data covering the period of 1994- 2015. The variables in the analysis were checked using Augmented Dickey Fuller test statistics. The results obtained indicated that economic growth became stationary at level while rene- wable energy consumption and trade openness variables became stationary at first difference. According to Todo-Yamamoto Causality Test results, there is a unidirectional causality from renewable energy consumption to economic growth at 5 % in the long run. This finding is in line with the growth theory which remarks unidirectional/one-way causality from renewa- ble energy consumption to economic growth. In this case, renewable energy dependent conservation policy may have prohibitive effect on economic growth. The study also concluded that there is no association between trade openness and economic growth. Thus, the finding su- pports the neo-classical growth theory. Besides, there is a causality from renewable energy co- nsumption to trade openness, so the conservation policies will affect the trade and trade liberalization policies designed to promote economic growth.
Keywords: F10; F18; O44; Q20; Q43; 330; renewable energy consumption; trade openness; economic growth; time series analysis; Bosnian economy